Peran Penyuluh Agama Islam dalam Mengusung Wasathiyyah Al-Islām: The Role of Islamic Extension in Carrying Wasathiyyah Al-Islām - lalu fahmi husein (Direktorat Jenderal Bimbingan Masyarakat Islam, 2014)
Build understand wasathiyyah al-Islam: ‘is (justice), at-tawazun (balance) and Tasamuh (tolerant) in religious field is the responsibility of the propagation of Islam, including Islamic Studies Extension. Extension of Islamic Studies should gradually play a role in changing the mindset of the target groups, addressing the differences in religion. Wasathiyyah is an attitude that is not showing the difference in executing religious teachings, reading Qur’an together and conduct religious activities together, is an indicator of the success of the propaganda by PAI.